Papua New Guinea food price bulletin: October 2024 - International Food Policy Research Institute; Kedir Jemal, Mekamu; Hayoge, Glen (International Food Policy Research Institute, 2024)
This report provides an analysis of food price trends for the third quarter of 2024, covering the period from July to September. During this quarter, two rounds of data were collected per month from Kokopo, Banz, and Port Moresby in July and August. However, in September, only one round of data was collected from all markets except Port Moresby (no data collected). Only one round of data was collected in Goroka for each month in the 3rd quarter. In Lae, food price data was collected only once in August for the entire third quarter. These data gaps affect the comparability of the reported price trend and caution should be used to draw conclusions on price fluctuations. The graphs in this bulletin show price changes within the third quarter and compare the third quarter prices with the second quarter of 2024, between April and June. To access the complete food price dataset and interactive food price graphing tool, please visit our website.